Op hom die groot hosannas : enkele aspekte van die modern Christelike poësie in Afrikaans - Bosman, Maria Elizabeth (Rhodes University, Faculty of Humanities, School of Languages, 1989)
This study is concerned with modern Christian poetry in Afrikaans. Afrikaans poetry, which initially carried the clear stamp of the Afrikaner's Calvinistic view of life, gradually assumed a new image to the extent that it could no longer be recognised as religious and specifically Calvinistic poetry. To the contrary, modern Afrikaans Christian poetry is the expression of a contemporary conceptualisation of the very same gospel. The occasional violent reaction especially of conservative institutions to so called "unchristian" modern poetry in Afrikaans during the past three decades, has prompted this study which attempts to illustrate that modern Afrikaans poetry still exhibits a strong Christian element. The essential qualities of contemporary Christian poetry in Afrikaans are illustrated in the discussion of the works of particular leading Afrikaans poets. Chapter 3 attempts to indicate a transitional stage between traditional and modern Christian poetry by means of an overview of the latest tendencies and approaches, with brief references to the recent poetry of the Louws, the poetry of Peter Blum as the initial exponent of the poetry of the Sixties, and the poetry of Ina Rousseau. The work of Sheila Cussons, eminent Roman Catholic (and thus also Christian) poet who is probably the most impressive contemporary exponent of metaphysical/mystic poetry in Afrikaans, is discussed in chapter 4. Chapter 5 illustrates the traditional Calvinistic Christian point of view and Christian experience as represented in the poetry of I.L. de Villiers. The poetification of the ministry adds new dimension to religions poetry in Afrikaans. Chapter 6 constitutes a discussion of the works of T.T . Cloete, the most significant contemporary Reformed poet in Afrikaans indicating the extent to which the many related facets embodied in his poetry consistently reflect a Christian attitude and are unified in and encompassed by the principle of Soli Deo Gloria. Chapter 7, by way of conclusion, reviews the religious poetry of Lina Spies and Petra Müller who write accessible popular poetry, nevertheless exploring interesting references. In conjunction with the poetry of Ina Rosseau, this poetry represents a contribution to modern Afrikaans religious poetry from a feminine point of view
Keywords: Afrikaans poetry -- History and criticism; Religious poetry, Afrikaans -- History and criticism; Christian poetry, Afrikaans; Calvinism in literature; Blum, Peter, 1925-1990; Rousseau, Ina; Cussons, Sheila; De Villiers, I. L., 1936-2009; Cloete, T. T. (Theunis Theodorus), 1924-2015; Spies, Lina; MuÌˆller, Petra, 1935-